Relationship Between Drop Jump Training–Induced Changes in Passive Plantar Flexor Stiffness and Explosive Performance - Ando, Ryosuke; Sato, Shinya; Hirata, Naoya; Tanimoto, Hiroki; Imaizumi, Naoto; Suzuki, Yasuhiro; Hirata, Kosuke; Akagi, Ryota (Frontiers in Physiology, 2021)
Passive muscle stiffness is positively associated with explosive performance. Drop jump training may be a strategy to increase passive muscle stiffness in the lower limb muscles. Therefore, the purpose of this study was to examine the effect of 8-week drop jump training on the passive stiffness in the plantar flexor muscles and the association between training-induced changes in passive muscle stiffness and explosive performance. This study was a randomized controlled trial. Twenty-four healthy young men were divided into two groups, control and training. The participants in the training group performed drop jumps (5 sets of 20 repetitions each) 3 days per week for 8 weeks. As an index of passive muscle stiffness, the shear moduli of the medial gastrocnemius and soleus were measured by shear wave elastography before and after the intervention. The participants performed maximal voluntary isometric plantar flexion at an ankle joint angle of 0° and maximal drop jumps from a 15 cm high box. The rate of torque development during isometric contraction was calculated. The shear modulus of the medial gastrocnemius decreased for the training group (before: 13.5 ± 2.1 kPa, after: 10.6 ± 2.1 kPa); however, such a reduction was not observed in the control group. There was no significant group (control and training groups) × time (before and after the intervention) interaction for the shear modulus of the soleus. The drop jump performance for the training group improved, while the rate of torque development did not change. Relative changes in these measurements were not correlated with each other in the training group. These results suggest that drop jump training decreases the passive stiffness in the medial gastrocnemius, and training-induced improvement in explosive performance cannot be attributed to change in passive muscle stiffness.